So Closely Related and Yet So Different: Strong Contrasts Between the Evolutionary Histories of Species of the Cardamine pratensis Polyploid Complex in Central Europe - Melichárková, Andrea; Šlenker, Marek; Zozomová-Lihová, Judita; Skokanová, Katarína; Šingliarová, Barbora; Kačmárová, Tatiana; Caboňová, Michaela; Kempa, Matúš; Šrámková, Gabriela; Mandáková, Terezie; Lysák, Martin A.; Svitok, Marek; et al. (Frontiers in Plant Science, 2020)
Recurrent polyploid formation and weak reproductive barriers between independent polyploid lineages generate intricate species complexes with high diversity and reticulate evolutionary history. Uncovering the evolutionary processes that formed their present-day cytotypic and genetic structure is a challenging task. We studied the species complex of Cardamine pratensis, composed of diploid endemics in the European Mediterranean and diploid-polyploid lineages more widely distributed across Europe, focusing on the poorly understood variation in Central Europe. To elucidate the evolution of Central European populations we analysed ploidy level and genome size variation, genetic patterns inferred from microsatellite markers and target enrichment of low-copy nuclear genes (Hyb-Seq), and environmental niche differentiation. We observed almost continuous variation in chromosome numbers and genome size in C. pratensis s.str., which is caused by the co-occurrence of euploid and dysploid cytotypes, along with aneuploids, and is likely accompanied by inter-cytotype mating. We inferred that the polyploid cytotypes of C. pratensis s.str. are both of single and multiple, spatially and temporally recurrent origins. The tetraploid C. majovskyi evolved at least twice in different regions by autopolyploidy from diploid C. matthioli. The extensive genome size and genetic variation of C. rivularis reflects differentiation induced by the geographic isolation of disjunct populations, establishment of triploids of different origins, and hybridization with sympatric C. matthioli. Geographically structured genetic lineages identified in the species under study, which are also ecologically divergent, are interpreted as descendants from different source populations in multiple glacial refugia. The postglacial range expansion was accompanied by substantial genetic admixture between the lineages of C. pratensis s.str., which is reflected by diffuse borders in their contact zones. In conclusion, we identified an interplay of diverse processes that have driven the evolution of the species studied, including allopatric and ecological divergence, hybridization, multiple polyploid origins, and genetic reshuffling caused by Pleistocene climate-induced range dynamics.